Breast cancer beliefs of women participating in a television-promoted mammography screening project. - Fuller, S M (1992)
A survey of breast cancer and breast cancer screening beliefs was mailed to a random sample of 1,000 women who contacted a telephone bank in response to a television-promoted, reduced-cost mammography project. Beliefs and demographics of women in the sample who subsequently completed a mammogram were compared with those who did not. No statistically significant differences were found between participants (persons who completed a mammogram) and nonparticipants with respect to age, race, marital status, income, or educational preparation. Groups also did not differ significantly in the series of beliefs examined. Factor analysis revealed respondents' most salient beliefs about breast cancer and early detection of breast cancer. Evidence is presented to suggest a need for enhanced efforts to recruit minority group women to participate in mammography screening.